2017
DOI: 10.14204/ejrep.37.14136
|View full text |Cite
|
Sign up to set email alerts
|

Navigation and Comprehension of Digital Expository Texts: Hypertext Structure, Previous Domain Knowledge, and Working Memory Capacity

Abstract: Introduction. In contemporary information societies, reading digital text has become perva-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
11
1
4
Order By: Relevance
“…Additionally, comprehension occurs when readers connect their prior knowledge to the text, make connections between different parts of the text, and make connections between known and unknown information [11]. While previous research has shown that there are profound positive relations between prior knowledge and reading comprehension [21,22,26], the results suggest that, in a more complex model of comprehension, there was no significant relationship between reading background knowledge and reading comprehension. Students' ackground did not contribute significantly to the prediction of reading comprehension in the path analysis model.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Additionally, comprehension occurs when readers connect their prior knowledge to the text, make connections between different parts of the text, and make connections between known and unknown information [11]. While previous research has shown that there are profound positive relations between prior knowledge and reading comprehension [21,22,26], the results suggest that, in a more complex model of comprehension, there was no significant relationship between reading background knowledge and reading comprehension. Students' ackground did not contribute significantly to the prediction of reading comprehension in the path analysis model.…”
Section: Discussionmentioning
confidence: 89%
“…In every new meeting with the text, the reader brings her/his total previous experiences to make meaning from the text [20]. Research has shown that comprehension is enhanced when readers activate and use prior knowledge to make connections with the text when reading [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Four expository texts were employed, similar in length and argumentative structure (around 720 words in 7 nodes: main concept, two secondary concepts, details about each concept, a conclusion relating both) (Burin, Barreyro, Saux, & Irrazábal, 2015). Given that the participants were completing an introductory cognitive psychology course, two texts presented familiar contents (language, memory: high prior knowledge condition) and the other two unfamiliar content (physics, astronomy: low prior knowledge condition) (Burin et al, 2015). In addition, each text could be presented with a hierarchical summary at the beginning with links to the different parts (text only), or a similar version with five colour decorative images (text with images).…”
Section: Methodsmentioning
confidence: 99%
“…Reading comprehension tasks Four expository texts with a similar argumentative structure (a general concept, two subordinate concepts, details about them, a general conclusion relating both) and length, around 710-720 words were employed (see Burin et al, 2015). Two versed on high (Memory, Language) and two on low (Astronomy, Physics) previous knowledge topics according to prior testing (Burin et al, 2013).…”
Section: Methodsmentioning
confidence: 99%